2010
DOI: 10.1017/s0032247410000665
|View full text |Cite
|
Sign up to set email alerts
|

Records of white-rumped sandpiper (Calidris fuscicollis) on the South Shetland Islands

Abstract: A programme to monitor non-breeding bird species in the vicinity of Arctowski Station, King George Island, South Shetlands, Antarctica, has been conducted over the past 30 years. The white-rumped sandpiper Calidris fuscicollis (Vieillot 1819) seems to occur now as a vagrant in South Shetlands area more frequently than previously. This trend, and the annual variation in numbers that have been observed could be a result of short term and longer term variation in weather and climate conditions during the austral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The consequences of these changes are generally expected to include: increased terrestrial diversity, biomass and trophic complexity, all of which contribute to more development of more complex ecosystem structure (Convey 2006). Combined with ameliorating growth conditions, the likelihood of colonisation by new populations of native and alien species is projected to increase in a warmer climate (Hughes et al 2006;Korczak-Abshire et al 2011). The two vascular plants native to the maritime Antarctic have provided the most studied examples of a measured biological response to the recent environmental warming in this region (McGraw and Day 1997;Gerighausen et al 2003).…”
mentioning
confidence: 99%
“…The consequences of these changes are generally expected to include: increased terrestrial diversity, biomass and trophic complexity, all of which contribute to more development of more complex ecosystem structure (Convey 2006). Combined with ameliorating growth conditions, the likelihood of colonisation by new populations of native and alien species is projected to increase in a warmer climate (Hughes et al 2006;Korczak-Abshire et al 2011). The two vascular plants native to the maritime Antarctic have provided the most studied examples of a measured biological response to the recent environmental warming in this region (McGraw and Day 1997;Gerighausen et al 2003).…”
mentioning
confidence: 99%
“…2) and after flying around the room several times it managed to escape and was never seen again. Ini− tially tentatively reported as a welcome swallow (H. neoxena) by Korczak−Abshire et al (2011), the bird was re−identified from photographs by A.C. Lees as an adult barn swallow Hirundo rustica of the New World subspecies erythrogaster. This ob− servation was subsequently accepted by the Avifaunistic Commission (the Polish Rarities Committee) as an adult female Hirundo rustica erythrogaster.…”
Section: Resultsmentioning
confidence: 99%
“…Alerstam 1990; Gilroy and Lees 2003;Lees and Gilroy 2009) or (3) may represent the vanguard of individuals pioneering new migration routes -"pseudo−vagrants" sensu Gilroy and Lees (2003), cf. Korczak−Abshire et al (2011), or finally (4) may be ship− −assisted for all or part of their journey (Shirihai 2008). A program to monitor bird species in the vicinity of the Polish Arctowski Station, on the western shore of Admiralty Bay, King George Island, South Shetlands, the Antarctic, has been conducted over the past 30 years (Myrcha and Teliga 1980;Jabłoński 1986;Trivelpiece et al 1987;Sierakowski 1991;Lesiński 1993).…”
Section: Introductionmentioning
confidence: 99%
“…There are several potential mechanisms by which vagrant individuals arrive in the Antarctic. They may have either drifted off course from their normal migration routes by austral gales (e.g., Lazo and Yañez 1989), traveling on errant headings (e.g., Lees and Gilroy 2009), or may represent the vanguard of individuals pioneering new migration routes-"pseudo-vagrants" sensu Gilroy and Lees (Gilroy and Lees 2003;Korczak-Abshire et al 2011a). They may be potential diaspore migration agents.…”
Section: System Contextmentioning
confidence: 99%
“…Providing a further climate warming the related factors, such as altered depth and extent of snow cover, permafrost melt, recession of glaciers, freeze-thaw cycles, and potential increase in the frequency and magnitude of extreme events, may influence plant and animal communities (see overview by Nielsen and Wall 2013). For example the white-rumped sandpiper Calidris fuscicollis with only sporadic visits has become more frequent on KGI and can be the first example of a natural species range shift (Korczak-Abshire et al 2011a;Trivelpiece et al 1987b). This trend could be the result of short term and longer term variations in weather and climate conditions during the austral spring and summer months, when this species is observed.…”
Section: Global Change-rapid Climate Change On King George Islandmentioning
confidence: 99%